2016
DOI: 10.1371/journal.pone.0162132
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Model of Asymptomatic Plasmodium Parasitemia That Recapitulates Elements of the Human Immune Response to Chronic Infection

Abstract: In humans, immunity to Plasmodium sp. generally takes the form of protection from symptomatic malaria (i.e., 'clinical immunity') rather than infection ('sterilizing immunity'). In contrast, mice infected with Plasmodium develop sterilizing immunity, hindering progress in understanding the mechanistic basis of clinical immunity. Here we present a novel model in which mice persistently infected with P. chabaudi exhibit limited clinical symptoms despite sustaining patent parasite burdens for many months. Charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…chabaudi infection. Among other subsets, we considered a role for CD4 + T helper cells, whose importance in controlling blood-stage Plasmodium has been suggested in humans [3032] and demonstrated in mice [33–37]; infected mice depleted of CD4 + T cells exhibit defects in parasite control reminiscent of those observed after late macrophage depletion [35,28,37,38] ( Fig 1D ). Accordingly, we found that depletion of CD4 + T cells 4 d.p.i.…”
Section: Resultsmentioning
confidence: 99%
“…chabaudi infection. Among other subsets, we considered a role for CD4 + T helper cells, whose importance in controlling blood-stage Plasmodium has been suggested in humans [3032] and demonstrated in mice [33–37]; infected mice depleted of CD4 + T cells exhibit defects in parasite control reminiscent of those observed after late macrophage depletion [35,28,37,38] ( Fig 1D ). Accordingly, we found that depletion of CD4 + T cells 4 d.p.i.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that Ifngr1 −/− mice chronically infected with P. chabaudi (patent parasitemia persisting >100 days) develop high frequencies of class-switched FCRL5 + B cells in the blood ( Fontana et al, 2016 ). To build on this observation, we performed global transcriptional profiling on class-switched, FCRL5 + or FCRL5 − B cells sorted from acutely infected Ifngr1 −/− mice 21 d.p.i., when FCRL5 + cells are abundant in circulation (gating in Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several lines of evidence support the contention that FCRL5 + murine MBCs are analogous to human atMBCs. Following a single Plasmodium infection, both populations expand in the blood and then contract as infection is cleared ( Figure 1C ; Scholzen et al, 2014 ; Sullivan et al, 2016 ), whereas chronic or repeated infection leads to a sustained increase in frequency ( Fontana et al, 2016 ; Weiss et al, 2009 ). When examined during acute infection, FCRL5 + B cells exhibit expression patterns comparable to human atMBCs for a substantial number of immune- related genes, perhaps most notably the master transcription factor T-bet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of inflammation appears to be dependent on the density of blood-stage infection and, by inference, P. falciparum biomass, as children with asymptomatic infection detectable by blood smear had higher levels of inflammation compared with uninfected children as well as children who were P. falciparum PCR positive but blood smear negative. Others have shown an association of asymptomatic P. falciparum infection in children with increased proportions of circulating CD16 + monocytes (43), anemia, and increased markers of systemic inflammation (44). Impaired phagocytosis by dendritic cells has been associated with submicroscopic parasitemia in malaria-naive adult volunteers experimentally challenged with P. falciparum-IEs (45).…”
Section: Cd16mentioning
confidence: 99%